Reducing Ship Queuing Time in Port Operation: A Modelling and Simulation Approach - Binti Mohamad, Fazeeda; Shahadah Binti Osman Mydin, Nurul; A.N.Aizat, Ahmad (International Journal of Engineering and Technology, 2018)
This study focuses on reducing queuing time in port operation by using discrete event simulation approach. This study was conducted to analyze the port operation activity in order to improve their performance in terms of time operation. A model was developed and simulated by mimicking the real port operation system using a case study. Two scenarios were experimented to see the effects or improvements in the queuing time of container loading and unloading activities. The result demonstrates the positive improvement on the queuing time for container to be loading and unloading.Â Â
Keywords: Queuing time; Simulation; ARENA software; Container loading and unloading; TEUs